Effect of polyethylene glycol capping on structural, optical and thermal properties of ZnS:Ni2+ nanoparticles. Issue 5 (11th April 2022) - Mohan, R.; Rakkappan, C.; Punitha, N.; Jayamoorthy, K.; Dhanalekshmi, K. I.
Abstract: To study the effect of polyethylene glycol capping on structural, optical and thermal properties, ZnS:Ni 2+ nanoparticles have been prepared by chemical precipitation method. It is demonstrated that by varying the concentration of PEG the particle size can be varied within ∼3.58 to 12 nm. To analyze the samples of nanostructures, the samples are subjected to X-ray diffraction, Field emission scanning electron microscopy and High resolution transmission electron microscopy characterization techniques. The spectral bands between 673 and 494 cm −1 are related to Zn-S stretching vibrations which was confirmed by Fourier transform infrared spectral studies. It is found that the uncapped sample emits strong UV light, whereas the capped samples exhibit strong and broad visible emission. An enhancement of fluorescence intensity has been obtained, in a capped sample with the minimum particle size and thus with more defect centers, in comparison to that of uncapped one.